Sistem Pakar Diagnosa Penyakit Hipoparatiroid Dengan Menggunakan Metode Certainty Factor - Hartania, Dwi (Jurnal Sains dan Teknologi Informasi, 2024)
Hypoparathyroidism is a disease in which the paratiroid gland in the body only emits a slight amount of the paratiroid hormone. Each person has four parathyroid glands located in the neck, near the thyroid. The paratiroid gland secretes the hormone paratiroid (PTH). In the human body the paratiroid hormone ACTS to maintain a balance of two minerals, calcium and phosphate. Calcium is needed to ensure the smooth operation of the nerves, muscles, and heart. Phosphate is needed in bone formation and teeth. As a result of the hypoparthyroid, the body will develop electrolytic dislytes of low levels of calcium (hypokalsemia) and high levels of phosphate (hyperphosphate). If found in the early stages, the disease is not a serious condition, although sufferers will need doctors' care and supervision throughout their life. In this study the authors wish to diagnose symptoms of hypoparatiroid disease by using systems of experts. The system of experts is a branch of computer-based artificial intelligence that employs specialized knowledge, facts and reasoning techniques in solving the problem of a particular expert in the field to solve a particular problem. In the system experts there is the Certainty Factor method that can prove whether a fact is certain or uncertain that is meant to diagnose the hypoparathyroid disease on the basis of its symptoms.